Institutional racism and black population health - Werneck, Jurema (Saúde e Sociedade, 2016)
The health of black women is not an area of knowledge or a relevant field in Health Sciences. The scientific knowledge production in this area is inexpressive and the theme is not part of the curriculum of different undergraduate and graduation programs in health, with very rare exceptions. It is a vague matter, which, in most cases, is ignored by most researchers, students, and health professionals in Brazil. This study intends to present some information on formulation processes of this conceptual field from the demands of organized social movements and experts' formulations. Such information will be presented with the aim of subsidizing research and contributing to the formulation and management of public policies suitable to the needs expressed in the social and health indicators of Brazilian black women.